2019
DOI: 10.1002/ffj.3492
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production of eugenol esters using enzymatic packed‐bed microreactors and an evaluation of the products as antifungal agents

Abstract: The enzymatic synthesis of biologically active compounds is receiving increasing interest from academic and industrial researchers. Herein, we report on the continuous‐flow enzymatic production of eugenol esters with packed‐bed microreactors prepared with the Novozym 435 and Lipozyme RM IM lipases. After optimization of the independent process variables, namely temperature (68 °C), flow rate (8 μL min−1), and eugenol/isobutyric anhydride molar ratio (1 : 5) by means of experimental design methodologies, the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…However, in high concentrations, it has an adverse effect of provoking inflammatory and allergic reactions, possibly due to its low instability, which favors the formation of phenoxyl radicals via its pro-oxidant activity [2,9]. Despite the fact that its structure is polyfunctional and readily accessible, eugenol is considered as a useful starting material for producing valuable derivatives through chemical synthesis [2,10,11,12,13,14,15] or biochemistry [1,4,9,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in high concentrations, it has an adverse effect of provoking inflammatory and allergic reactions, possibly due to its low instability, which favors the formation of phenoxyl radicals via its pro-oxidant activity [2,9]. Despite the fact that its structure is polyfunctional and readily accessible, eugenol is considered as a useful starting material for producing valuable derivatives through chemical synthesis [2,10,11,12,13,14,15] or biochemistry [1,4,9,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol derivatives can be obtained by reactions on the hydroxyl group of its structure via acetylation [4,15,19] or benzoylation [2,9,20]. Investigations have shown that this modification also improves antioxidant and larvicidal activities 2 or 5 times, respectively, moreover to the reduced level of cytotoxicity compared to its precursor, eugenol [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Effective esterification of eugenol in solventless systems has been reported, with augmented antimicrobial activity against several bacteria compared to pure eugenol [23]. Encouraging results were also obtained considering the antifungal activity of the eugenol isobutyryl and acetyl esters that inhibit dermatophytes M. gypseum and T. mentagrophytes growth [24]. The scientific literature reports several works where C. antarctica lipase B performed efficiently as a biocatalyst of esterification reactions [25].…”
Section: Introductionmentioning
confidence: 99%
“…The use of waste water from the clove bud steam distillation process is environmentally friendly and allows us to apply the waste, containing valuable biologically active compounds. These compounds, due to their mechanism of action, can have a beneficial effect on the balance between oxidants and antioxidants in the body, minimizing the effects of oxidative stress (Ivy and Payne, 1991;Dahham et al, 2015;Sarpietro et al, 2015;Giovannini et al, 2019;Razafindrakoto et al, 2020). The use of cream and gel vehicles for this type of research is, therefore, justified; moreover, the pH value of the acceptor phase in permeation in vitro tests was set at 7.4 for simulation of the skin surface (Ossowicz et al, 2020;Nowak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%